Evaluasi dan Perencanaan Saluran Drainase Menggunakan Program Bantu EPA SWMM 5.0 (Wilayah Kajian : Jalan Suka Karya km 0-km 5) - Suryafit, Sagit; Suprayogi, Imam; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Flooding is a major problem that has potential to occur during the rainy season. Replanning of drainage channel dimensions in Jalan Suka Karya km 0-km 5 can be used as an effort to control flood problems. The purpose of this study is to evaluate the existing condition of the drainage channel that caused flooding in the study site and determine an alternative solution if the existing condition of thedrainage channel is unable to accommodate rainwater runoff discharge. The hydrological analysis of this plan used the Log Person III probability distribution and used a 5-year return period. The EPA SWMM assistance program was used to analyze flood problems at the study site. The problem of flooding that occurred at the study site was caused by problems with the dimensions and material thatwere not uniform, as well as sedimentation on the surface of the drainage channel. Land use conditions in the form of densely populated residential areas caused some drainage canals in the study site to be closed by construction buildings that were part of the shoulder of the road so that the drainage system cannot accommodate and excess water optimally. According to the evaluation results of the EPA SWMM assistance program by replanning the dimensions ofthe drainage channel would overcome the problem of flooding in the study site. The drainage channel using U-Ditch precast concrete with dimensions of 0.8 m x 1 m. The engineer estimate required in the drainage channel planning construction is Rp. 12,197,249,000.00.Keywords: EPA SWMM, Hydrology Analysis, Drainage Dimensions, Engineer estimate